Pengaruh Model Pembelajaran Numbered Head Together Terhadap Hasil Belajar Siswa pada Mata Pelajaran Ipas Kelas V SD Swasta Al-Washliyah 80 Kisaran - Rana Rafiqa; Robenhart Tamba; Lala Jelita Ananda; Lidia Simanihuruk; Doddy Feliks P. Ambarita (Lembaga Pengembangan Kinerja Dosen, 2025)
The study was conducted with the aim of determining whether there is an influence of the Numbered Head Together learning model on the learning outcomes of fifth grade students of SDN Swasta Al-Washliyah 80 Kisaran. Descriptive quantitative research in this study used an experimental research design with a Quasi Experiment Design model in the form of Non-equivalent Control Group Design. The population in this study was all fifth grade students of SDN Swasta Al-Washliyah 80 Kisaran. The results of data analysis showed that the average learning outcomes using the Numbered Head Together learning model in the experimental class were 85.7, while the average learning outcomes that did not use the Numbered Head Together learning model in the control class were 69.1. In the normality test, it is known that the pre-test and post-test results of the experimental class and control classes are normally distributed with the value obtained in the experimental class pre-test Test results = 0.051> α = 0.05 and in the post-test results Test results = 0.061> α = 0.05, while in the control class pre-test Test results = 0.057> α = 0.05 and in the post-test results Test results = 0.118> α = 0.05. The results of the homogeneity test of the research data, it is known that the research data comes from homogeneous samples with the acquisition of a homogeneity test value of 0.219> 0.05. The data were analyzed by hypothesis testing using the independent sample t-test with a significance level of α = 0.05 and degree of freedom (df) = 48. From the results of the hypothesis test, it was obtained tcount> ttable (4.056> 2.565) or Ha was rejected and H1. So it can be stated that there is a positive and significant influence between the implementation of the Numbered Head Together learning model on the learning outcomes of class V students of SD Swasta l-Washliyah 80 Kisaran.